Evaluating the Effect on Total Daily Insulin Dose in Adult Patients with Type 1 Diabetes Managed with Metformin and/or GLP-1 or GLP-1/GIP Receptor Agonists - Mayeesha Ahmed; Emily Pierson; Molly Webster (INNOVATIONS in Pharmacy)
Purpose: